2010
DOI: 10.1371/journal.pone.0009445
|View full text |Cite
|
Sign up to set email alerts
|

Dimensionality Controls Cytoskeleton Assembly and Metabolism of Fibroblast Cells in Response to Rigidity and Shape

Abstract: BackgroundVarious physical parameters, including substrate rigidity, size of adhesive islands and micro-and nano-topographies, have been shown to differentially regulate cell fate in two-dimensional (2-D) cell cultures. Cells anchored in a three-dimensional (3-D) microenvironment show significantly altered phenotypes, from altered cell adhesions, to cell migration and differentiation. Yet, no systematic analysis has been performed that studied how the integrated cellular responses to the physical characteristi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
89
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 86 publications
(93 citation statements)
references
References 52 publications
4
89
0
Order By: Relevance
“…The 3D culture has similarly been shown to be a strong signal in a number of other cell lines. [22][23][24][25] Wound-healing response (a-SMA) is downregulated in both low-and high-density cultures Our density study results show that the wound-healing response is downregulated in the 3D culture both at low seeding density and at high seeding density when compared with intermediate seeding densities and normal TC culture (Fig. 4C).…”
Section: D Culture Environment Promotes Partial Recovery Of Keratocymentioning
confidence: 69%
See 1 more Smart Citation
“…The 3D culture has similarly been shown to be a strong signal in a number of other cell lines. [22][23][24][25] Wound-healing response (a-SMA) is downregulated in both low-and high-density cultures Our density study results show that the wound-healing response is downregulated in the 3D culture both at low seeding density and at high seeding density when compared with intermediate seeding densities and normal TC culture (Fig. 4C).…”
Section: D Culture Environment Promotes Partial Recovery Of Keratocymentioning
confidence: 69%
“…It has been well established that the observed cell phenotype changes when the 2D and 3D cell cultures are compared for a given cell population, [22][23][24] including human foreskin fibroblasts. 25 We hypothesized that by placing a subcultured corneal cell population in a 3D environment, we could downregulate the myofibroblast phenotype.…”
mentioning
confidence: 99%
“…A recent study has shown that the level of confinement below which cells have difficulties to form stress fibres is lower in 3D microwells than in 2D micropatterns, supporting the idea that stimulation along the z-axis matters (Ochsner et al, 2010). However, in these experiments, the difference in the ability of a cell to form stress fibres is only visible when the microwells are molded in soft polymers and not when rigid polymers are used, indicating a crucial role for the stiffness of the microenvironment in organizing the cellular actin architecture.…”
mentioning
confidence: 86%
“…After washing with PBS and distilled water, samples were mounted and examined and photographed with CLSM using a 63× oil immersion objective. To assess the degree of rearrangement of Col I by hADSCs a method was adapted from published papers [29,30], with quantification being performed in ImageJ. Briefly, the images were first normalised to ensure the same total range of pixel values.…”
Section: Remodeling Of Type I Collagen (Col I) By Hadscsmentioning
confidence: 99%